مجلس المحاسبة والتدقيق في سورية، الواقع والتطوير - حسن يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى معرفة واقع عمل مجلس المحاسبة والتدقيق في سورية وإلى تحديد الجوانب الواجب تطويرها في مجلس المحاسبة والتدقيق ليستطيع رفع مستوى أداء المهنة في ظل التطورات التي تشهدها البلاد. اعتمدت الدراسة المنهج التحليلي الوصفي فتم تحليل ما ورد في القانون 33 بما يخص مجلس المحاسبة والتدقيق، ثم أُجريت عملية التحليل ذاتها على ضوابط ممارسة المهنة بما يخص الجهة المشرفة في كل من الولايات المتحدة الأمريكية باعتبار أن مستوى المهنة فيها متطور جداً وله خصوصياته، وفي الأردن باعتبار أن ظروف ممارسة المهنة فيه مشابهة إلى حد كبير لظروف بيئة الأعمال السورية. ثم تم مقارنة نتائج التحليل وتوصلت الدراسة إلى أن هناك عدة نقاط ضعف في آلية عمل المجلس منها عدم الاستقلال التام لأعضائه وعدم تفعيل دور اللجان الملحقة بشكل جيد. The objective of the research is to know the reality of the work of the Accounting and Auditing Board in Syria and to identify the aspects to be developed in the Audit and Audit Council so as to raise the level of performance of the profession in light of developments in the country. The study was based on the descriptive analytical method. The analysis of what was stated in Law 33 regarding the Accounting and Auditing Board was analyzed. The same analysis was conducted on the rules of practicing the profession regarding the supervising authority in the United States of America, considering that the level of the profession is highly developed and has its specificities. That the conditions of practicing the profession is very similar to the circumstances of the Syrian business environment. Then the results of the analysis were compared and the study found that there are several weaknesses in the mechanism of the work of the Council, including the lack of full independence of its members and not activate the role of the attached committees well.